First fundamental rights documents in Europe : commemorating 800 years of Magna Carta / Markku Suksi, Kalliope Agapiou-Josephides, Jean-Paul Lehners, Manfred Nowak (eds). - Suksi, Markku, 1959-; Agapiou-Joséphidés, Kalliope; Lehners, Jean-Paul; Nowak, Manfred, 1950- (Intersentia, 2015)
With the spotlight on Magna Carta, which is 800 years old in 2015, and the French Declaration of the Rights of Man and Citizen of 1789, which together are of undeniable importance for fundamental rights-thinking, the existence of similar fundamental rights documents in other European countries is often overlooked. Such fundamental rights documents did, however, exist in the precursors to the current European Union Member States. Some of the documents are ancient, even older than Magna Carta, and some are more recent, but all of them are texts that deserve to be brought out and analysed alongside Magna Carta and the French Declaration in order to better understand the evolution of fundamental rights thinking in Europe.This volume paints a multi-faceted picture of historical fundamental rights documents in the European space by collating the experience of 24 European Union Member States at times in history when most of these states did not even exist. It is the first comprehensive and systematic evaluation of early fundamental rights thinking across Europe and it reveals surprising diversity. Spanning documents from the fifth century BC right through to the 19th century and early 20th century AD, this review opens up themes not normally found in historiographical analyses of fundamental rights.